(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: The relation between the increased out-of-home food consumption and the rising of overweight and obesity prevalence rates has been widely assessed, and the a key role played by the catering sector in ensuring healthy food choices has been recognised. Governments’ healthy eating policies have a wide range of action, influencing consumer behavior, and the socioeconomic and food environments, with specific actions for the catering sector. Information on the public support for these policies could help policy makers in planning decisions. This study aims to investigate the relationship of out-of-home eating frequency with beliefs about obesity causes, support to healthy eating policies, and with socio-demographic factors. Methods: Data on 3003 individuals from Belgium, Denmark, Italy, Poland and United Kingdom, of both sexes, aged ≥16 years, were employed, from the European survey on policy preferences (Eatwell). Data were analysed through Chi-square test and logistic regression analysis. Results: Out-of-home eating varied with gender, age, marital status, education, BMI, and by country. Convenience food consumption was positively associated with obesity attribution to genetics, and inversely associated with attribution to lack of willpower. Attributions of obesity to lack of time, and to lack of self-control were associated with increased likelihood to consume fast-food and ready-prepared food respectively. Out-of-home eating people expressed higher support for information-based prevention, and actions aimed at healthier out-of-home eating, and lower support for restrictions and regulations of the food supply environment. Conclusion: Future research on out-of-home food consumers and their support towards public interventions for the catering sector, could have important implications for effective strategies to promote healthy eating.